Answer:
The 2nd answer choice is the correct one.
Explanation:
f(x) = –(x + 3)(x + 1), when multiplied out, becomes f(x) = -(x^2 + 4x + 3), or
f(x) = -x^2 - 4x - 3. Because of the - sign, the graph opens downward.
Because of the factor (x + 3), the graph goes through (-3, 0).
Because of the factor (x + 1), the graph goes through (-1, 0).
The vertex is located horizontally exactly betwen x = -3 and x = -1, that is, at x = -2. Since f(-2) = -(-2)^2 - 4(-2) - 3, the max value of f is -4 + 8 - 3, or 1. Thus, the vertex is located at (-2, 1). This matches the 2nd answer choice.